2013
DOI: 10.1039/c3sm52173g
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomic aging behaviour in a colloidal glass

Abstract: An unexpected dichotomic long time aging behaviour is observed in a glassy colloidal clay suspension investigated by X-ray photon correlation spectroscopy and dynamic light scattering. In the long time aging regime the intensity autocorrelations are non-exponential, following the Kohlrausch-Williams-Watts functional form with an exponent beta(Q). We show that for spontaneously aged samples a stretched behaviour (beta(Q) < 1) is always found. Surprisingly a compressed exponent (beta(Q) > 1) appears only when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 27 publications
13
65
0
Order By: Relevance
“…While a stretched behaviour with bo1 has been reported for spontaneously aged samples at all waiting times, a surprising behaviour is found for the rejuvenated samples upon varying the rejuvenation time, t R . Samples rejuvenated before a certain critical time t c show a stretched behaviour (bo1) while samples rejuvenated after t c exhibit a compressed behaviour (b41) in agreement with a recent study 31 . This is shown in the inset of Fig.…”
Section: Dilution Experimentssupporting
confidence: 91%
“…While a stretched behaviour with bo1 has been reported for spontaneously aged samples at all waiting times, a surprising behaviour is found for the rejuvenated samples upon varying the rejuvenation time, t R . Samples rejuvenated before a certain critical time t c show a stretched behaviour (bo1) while samples rejuvenated after t c exhibit a compressed behaviour (b41) in agreement with a recent study 31 . This is shown in the inset of Fig.…”
Section: Dilution Experimentssupporting
confidence: 91%
“…While a stretched shape would suggest a distribution of Brownian diffusors, with a heterogeneous distribution of relaxation times, the transition to a compressed shape, accompanied by n ≈ 1 is a signature of an arrested system. Similar stretched-compressed dynamical crossovers have been also reported in a few different out-of-equilibrium materials such as nanoparticles in a glass-former matrix [35], metallic glasses [36], and, very recently, in Laponite suspensions by Angelini et al [37]. In the last, the authors observed γ ≈ 0.75 in an aged Laponite suspension (C w = 3.0%), while rejuvenation by means of mechanical perturbation seems to induce a more compressed shape (γ = 1.5 at low q, decaying to 1.25 as q increases).…”
Section: B Intrinsic Dynamics Probed By Gi-xpcssupporting
confidence: 80%
“…In this scenario, the stretched exponential behaviour observed in NS4 might be related to its stress-free nature, as discussed in topological approaches to the glassy network 25,26 . A similar compressed/stressed and stretched/ stress-free scenario has been recently proposed for a colloidal suspension of Laponite under an external shear field 43 . Finally, it is worth noticing that the very same absence of visible physical aging at the microscopic scale has been also detected after long annealing in metallic glasses 20,21 .…”
Section: Resultsmentioning
confidence: 56%